An expanded study of long‐pulsed 1064 nm Nd:YAG laser treatment of basal cell carcinoma. Issue 7 (13th February 2018) - Ortiz, Arisa E.; Anderson, R. Rox; DiGiorgio, Catherine; Jiang, Shang I. Brian; Shafiq, Faiza; Avram, Mathew M.
Abstract : Background and Objective: Basal cell carcinoma (BCC) is an indolent form of skin cancer that is rarely life threatening, but can cause significant cosmetic and functional morbidity. Surgical treatments often result in disfiguring scars, while topical therapies frequently result in recurrence. The need for a more effective nonsurgical alternative has led to the investigation of laser treatment of BCC. We have previously conducted a pilot study which showed 100% histologic clearance at high fluences. Treatments were well tolerated with no significant adverse events. The objective of this larger study was to confirm preliminary results that the 1064 nm Nd:YAG laser is a safe and effective method for treating non‐facial BCC. Design: This is an IRB‐approved, prospective, multi‐center study evaluating the safety and efficacy of the 1064 nm Nd:YAG laser for the treatment of BCC on the trunk and extremities. Thirty‐three subjects seeking treatment for biopsy‐proven BCC that did not meet the criteria for Mohs surgery were recruited. Subjects on current anticoagulation therapy, or with a history of immunosuppression were excluded. Subjects received one treatment with the 1064 nm Nd:YAG laser as follows: 5–6 mm spot, fluence of 125–140 J/cm 2 and a pulse duration of 7–10 ms. Standard excision with 5 mm clinical margins was performed at 30 days after laser treatment to evaluate clinical and histologic clearance of BCC. Standardized photographs and adverse assessments were taken at the baseline visit, immediately after laser treatment and on the day of excision. Results: Thirty‐one subjects completed the study. BCC tumors had a 90% (28 of 31 BCC tumors) histologic clearance rate after one treatment with the long‐pulsed 1064 nm Nd:YAG laser. Treatments were generally well tolerated without any anesthesia. Immediate side effects included edema and erythema. At 1‐month follow‐up, some patients had residual crusting. No significant adverse events occurred. Conclusion: The 1064 nm long‐pulsed Nd:YAG laser is an alternative for treating non‐facial BCC for those that are poor surgical candidates. Lasers Surg. Med. 50:727–731, 2018. © 2018 Wiley Periodicals, Inc.